Factors Determining College Students’ Intention to use E-Wallets - Dewi Khornida Marheni; Candy Candy; Julia Rahayu Putri; Marcelino Marcelino; Dhifira Annisa Widyasari (Almana : Jurnal Manajemen dan Bisnis, 2022)
E-Wallet users in Indonesia are experiencing explosive growth due to the ease of registration, ease of use, and exclusive promotions and offers available to E-Wallet users. E-Money or E-Wallet service providers also vary. Each has its characteristics, so this study aims to analyze the relationship between perceived usefulness, perceived ease of use, trust, and social influence on intentions to use electronic wallets in Batam International University students. The population in this study is Batam International University students with a sample of 250 using the rule of thumb theory. Data retrieval using primary data types and analyzed using multiple linear regression analysis. This study shows that perceived ease of use and social impact are positively significant on the intention to use E-Wallet. While the benefits and perceived trust do not show significance.